Bovine Viral Diarrhea Virus in Zoos: A Perspective from the Veterinary Team - Kottwitz, Jack J.; Ortiz, Melissa (Frontiers in Microbiology, 2016)
The many different species in close proximity make zoological collections a unique environment for disease transmission. Bovine Viral Diarrhea Virus (BVDV) is of special concern with zoos due to the numerous exotic ruminant species that this virus can infect. BVDV occurs as both a non-cytopathic and a cytopathic strain both of which are capable of infecting exotic ruminants. The cytopathic strain causes mucosal disease (MD) and death. Infection with the non-cytopathic strain may produce persistently infected (PI) animals. PI individuals may show vague clinical signs, including abortion. Management of BVDV in zoos should focus on identification of PI individuals and prevention of infection of other animals of the collection. Variability makes serological testing as the sole method of screening for BVDV infection undesirable in exotic ruminants. Combination testing provides a definitive answer, especially in sensitive wildlife. Use of a combination of antigen-capture ELISA (ACE) with haired skin, Real Time-PCR (RT-PCR) on whole blood, and antibody detection via serum neutralization has the greatest potential to identify PI animals. An animal that is positive on both ACE and RT-PCR, but is negative on serology should be considered highly suspicious of being a PI, and should be isolated and undergo repeat testing 4–6 weeks later to confirm positive status. This testing methodology also allows screening of pregnant and newborn animals. Isolation or culling may need to be considered in animals determined to be positive via combination testing. These decisions should only be made after careful consideration and evaluation, especially with endangered species.